ANALISIS MINAT KONSUMEN TERHADAP PEMBELIAN ULANG PRODUK COCA-COLA KEMASAN KELUARGA DI WILAYAH SEMARANG - DENNY SEPTA (Jurnal Bisnis dan Akuntansi, 2004)
In this research, receacher analyzed a model witch had factors that affected consumer satisfaction and also product repurchase at the end of thr process. Bolton and Drew (1991, p.875) indicated that the factors were a construct, and we agreed that people tend to do product repurchase activity because of higher product quality. Based on research background, the research problem was developed and became an issue of this study. The research problem is how to conceptualize the product quality, consumer satisfaction and its dimensions, and could contextually product quality and service quality influence satisfaction based on consumer need in order to increase product repurchase. To answer the question on this study, research model was developed. The model has four dimension: product quality, service quality, consumer satisfaction and repurchase with tree hipotesis tested. Data analysis over 100 respondents who have already consumed Coca-Cola beverage (home consumption package) in Pasadena and Tlogosari area in emarang was done using Structural Equation Modeling as analysis tool an AMOS 4.01 program. The result showed that all hipotesis tasted was not rejected, and we concluded that product and service quality has a positif impact for consumer satisfaction and product repurchase. This research also resulted in managerial implication for all PT. Cola-Cola Amatil Indonesia, and well find it at conclusion chapter. This research also has limitation and the suggestion for the next researchers.